2016
DOI: 10.1063/1.4960531
|View full text |Cite
|
Sign up to set email alerts
|

Broadband transverse electric surface wave in silicene

Abstract: Transverse electric (TE) surface wave in silicine is theoretically investigated. The TE surface wave in silicene is found to exhibit better characteristics compared with that in graphene, in terms of a broader frequency range and more confinement to the surface which originate from the buckled structure of silicene. We found that even undoped silicene can support the TE surface wave. We expect to obtain the similar characteristics of the TE surface wave in other two-dimensional materials that have slightly buc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…These facts unavoidably limit their practical applications. Actually, although the work in 2007 ignited many researches of TE plasmon polaritons in graphene [15][16][17][18] and other 2D materials [19][20][21], only a few of their potential nanophotonic applications have been reported, such as polarizers [22], waveguide phase and amplitude modulators [23], optical sensors [24] and Brewster effects [25]. Therefore, it is highly desirable yet challenging to enhance the spatial confinement of TE polaritons, which can further enable their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…These facts unavoidably limit their practical applications. Actually, although the work in 2007 ignited many researches of TE plasmon polaritons in graphene [15][16][17][18] and other 2D materials [19][20][21], only a few of their potential nanophotonic applications have been reported, such as polarizers [22], waveguide phase and amplitude modulators [23], optical sensors [24] and Brewster effects [25]. Therefore, it is highly desirable yet challenging to enhance the spatial confinement of TE polaritons, which can further enable their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ukhtary et al showed that by applying , TE waves can be propagated in a larger frequency range for silicene. While the TE wave propagation range for graphene is only possible in a narrow frequency range of 49 , it can be increased for silicene by increasing . Hence, an OMOSFET was designed in the present study using this feature of silicene.…”
Section: Device Modelingmentioning
confidence: 99%
“…According to for TE waves 49 , where is the optical confinement length and is the vacuum permeability, better propagation of surface waves occurs at smaller values of . As a result, larger values of the imaginary part of conductivity ( ) provide smaller values of the confinement length.…”
Section: Device Modelingmentioning
confidence: 99%
“…This way, highly confined graphene plasmons can be achieved without stringent requirement on the polarization of light and can benefit more practical applications based on TE waves. Such a quest still remains elusive, although many researches of TE polaritons in graphene [26][27][28][29] and other 2D materials [30][31][32][33][34] have been ignited by the pioneering work in 2007.…”
Section: Introductionmentioning
confidence: 99%